2009
DOI: 10.1111/j.1365-2893.2009.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography and other noninvasive tests to assess hepatic fibrosis in patients with viral hepatitis

Abstract: The limitations of liver biopsy (invasive procedure, sampling errors, inter-observer variability and nondynamic fibrosis evaluation) have stimulated the search for noninvasive approaches for the assessment of liver fibrosis in patients with viral hepatitis. A variety of methods including the measurement of liver stiffness, using transient elastography, and serum markers, ranging from routine laboratory tests to more complex algorithms or indices combining the results of panels of markers, have been proposed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
111
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 156 publications
(199 reference statements)
7
111
1
6
Order By: Relevance
“…In a recent study, it was reported that the cut-offs for cirrhosis range from 9 kPa in HBV patients to 26.5 kPa in HCV-liver transplant patients. These could be related to the lower amount of fibrosis in HBV-related cirrhosis [22]. In the subgroup analysis of our study, the AUROC for predicting cirrhosis in HBV patients was lower than that for predicting cirrhosis in HCV patients (0.678 vs 0.930, respectively), although the number of HCV patients was small (92 vs 29).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In a recent study, it was reported that the cut-offs for cirrhosis range from 9 kPa in HBV patients to 26.5 kPa in HCV-liver transplant patients. These could be related to the lower amount of fibrosis in HBV-related cirrhosis [22]. In the subgroup analysis of our study, the AUROC for predicting cirrhosis in HBV patients was lower than that for predicting cirrhosis in HCV patients (0.678 vs 0.930, respectively), although the number of HCV patients was small (92 vs 29).…”
Section: Discussioncontrasting
confidence: 54%
“…Fibroscan has been reported to be the most reliable noninvasive method for detecting cirrhosis [22,25]. But other researchers have demonstrated that the diagnostic performance of Fibroscan was similar to that of the surrogate serum marker panels [21,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Patients whose bilirubin exceeds 4 mg/dL in the early posttransplant period have been shown to have greatly increased …”
mentioning
confidence: 99%
“…reason why the GSA index did not show well discriminative ability between patients with F2 and F3 is unclear, however, the small sample size in patients with F2 (n=19) may be attributed to our current results. Liver biopsy, which has been considered as the 'golden standard' for assessing the extent of liver fibrosis, carries some drawbacks: sampling error and interobserver variability, which have raised questions on its value, whereas in our present analyses, we investigated the impact of the preoperative GSA index on cirrhosis using non-tumor parts of extracted surgical specimens, which had sufficient amount of liver specimens for exact evaluation of the degree of liver fibrosis (30)(31)(32). Thus, our data are highly reliable and this is a major strength of the present study.…”
Section: Discussionmentioning
confidence: 99%